Cancer epidemiology and the workplace - FRUMKIN HOWARD (Instituto Nacional de Salud Pública, 1997)
Occupational exposure occurs most frequently through direct contact with carcinogenic agents, with any of their active metabolites during absorption (skin, respiratory tract); or during excretion (urinary tract). In the USA, from 2-8% of cancer are attributed to this circumstance. In developing countries emphasis should be made on prevention measures of possible carcinogenic exposure factors, with three basic premises: a) identify exposure markers (biological monitoring); b) identification of high risk subjects, presumable before exposure occurs, and c) early identification of signs of sickness (medical surveillance). This article proposes that, in theory, all occupational cancer can be prevented.